Progress in the Development of Stem Cell-Derived Cell-Free Therapies for Skin Aging - Chou Y; Alfarafisa NM; Ikezawa M; Khairani AF (Clinical, Cosmetic and Investigational Dermatology, 2023)
Yoan Chou,1 Nayla Majeda Alfarafisa,2 Maiko Ikezawa,3 Astrid Feinisa Khairani1,2 1Graduate School of Master Program in Anti Aging and Aesthetic Medicine, Faculty of Medicine, Universitas Padjadjaran, Jatinangor, West Java, Indonesia; 2Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Jatinangor, West Java, Indonesia; 3Department of Anatomy and Cell Biology, Graduate School of Medicine, Gunma University, Gunma, JapanCorrespondence: Astrid Feinisa Khairani, Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Jalan Raya Bandung – Sumedang Km 21, Jatinangor, West Java, 45363, Indonesia, Tel +62-22-7795594, Email astrid.khairani@unpad.ac.idIntroduction: The skin is a vital organ as the body’s largest barrier, but its function declines with aging. Therefore, research into effective regeneration treatments must continue to advance. Stem cell transplantation, a cell-based therapy, has become a popular skin-aging treatment, although it comes with drawbacks like host immune reactions. Stem cell-derived cell-free therapies have emerged as an alternative, backed by promising preclinical findings. Stem cell secretomes and extracellular vesicles (EVs) are the key components in cell-free therapy from stem cells. However, comprehensive reviews on the mechanisms of such treatments for skin aging are still limited.Purpose: This review discusses stem cell-derived cell-free therapy’s potential mechanisms of action related to skin aging prevention by identifying specific molecular targets suitable for the interventions.Methods: A search identified 27 relevant in vitro studies on stem cell-derived cell-free therapy interventions in skin aging model cells without restricting publication years using PubMed, Scopus, and Google Scholar.Results: Stem cell-derived cell-free therapy can prevent skin aging through various mechanisms, such as (1) involvement of multiple regenerative pathways [NFkb, AP-1, MAPK, P-AKT, NRF2, SIRT-1]; (2) oxidative stress regulation [by reducing oxidants (HO-1, NQO1) and enhancing antioxidants (SOD1, CAT, GP, FRAP)]; (3) preventing ECM degradation [by increasing elastin, collagen, HA, TIMP, and reducing MMP]; (4) regulating cell activity [by reducing cell senescence (SA-β-gal), apoptosis, and cell cycle arrest (P53, P12, P16); and enhancing autophagy, cell migration, and cell proliferation (Ki67)] (5) Regulating the inflammatory pathway [by reducing IL-6, IL-1, TNF-⍺, and increasing TGF-β]. Several clinical trials have also revealed improvements in wrinkles, elasticity, hydration, pores, and pigmentation.Conclusion: Stem cell-derived cell-free therapy is a potential novel treatment for skin aging by cell rejuvenation through various molecular mechanisms. Keywords: cell-free therapy, extracellular vesicles, secretome, skin aging, stem cell